Bilateral strength balance of knee extensor and flexor muscles in female soccer players - Andrades-Ramírez, Oscar; Ulloa-Díaz, David; Romero-Vera, Luis; Alfaro-Castillo, Bryan; Muñoz-Bustos, Gustavo; Jorquera-Aguilera, Carlos; Carvajal-Parodi, Claudio; Chirosa-Ríos, Luis-Javier (Frontiers in Physiology, 2025)
BackgroundThe aim of our study was analyze the bilateral strength balance of the knee extensor and flexor muscles in female soccer players.MethodologyParticipated in this study twenty-three professional female soccer players. The volunteer participants of the study were eligibly if: (a) signing of informed consent, (b) 5 years of sporting experience as a soccer player and have experience with training and evaluation of muscle strength in the lower limb, (c) participate in five weekly training sessions (d) no musculoskeletal pathology in the lower limbs 6 months prior to the evaluation date. The assessment was performed unilaterally, with peak muscle strength values recorded using the FEMD device software at a constant velocity of 0.4 m s-1. The range of motion (ROM) was 90°–0° of joint extension in the sitting position and 150°–90° of flexion in the prone position. Each participant was required to perform their maximum effort for all repetitions.ResultsBilateral strength balance measurements were obtained in the range of 10.68%–13.80% for maximum muscle strength in knee extension and 13.27%–15.21%. No significant differences (p > 0.05) were found in the comparison of independent means for maximum muscle strength between the knee extension and flexion in the concentric and eccentric phases. Significant differences (p < 0.01) and small ES (ES < 3.32) were found in peak muscle strength measurements of the dominant and non-dominant lower extremity in the unilateral comparison of the extensor muscle and the flexor muscle group in the concentric and eccentric phase.ConclusionIn the analysis of bilateral strength balance, lower indices are presented in the knee extensor compared to the flexor, these bilateral indices would reveal intrinsic and extrinsic risk factors for musculoskeletal injuries in the hamstring muscles and anterior cruciate ligament of professional soccer players.